(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud computing is emerging as a critical information communication technology to heavily impact our daily life in the future. It is an emerging trend in computing. This is happening at a time when there is increasing attention being paid to the need to manage energy consumption across the entire information and communication technology (ICT) sector. Data center energy has received much attention recently because there are very huge data centers used in industries today and environmentally, these systems can produce e-waste, harmful gases with heat. This paper focuses on different techniques to save over all energy consumption in the data centers, in the enterprises it is called as green cloud computers. Here i have explained and suggested the virtualization technique for saving energy, thus faciliating green cloud computing.